TRANSFER EQUATIONS APPLYING TO LAYERED MEDIA SOUNDING PROBLEMS - Bakut P.A.; Ershova O.M.; Shumilov Yu.P. (My University, 2003)
The sounding problem of 1-D layered media has been solved with wave energy transfer equations. Forward and backward wave propagation at any trajectory point are calculated. Analytical solutions for simple trajectories are derived. In the general case the solutions can be determined numerically. For certain active seismic sounding problem having good data coverage, this algorithm can be used to invert for characteristics of the layered media.